Fluid Workers in Indonesia: Benefits, Challenges, and Needs in Digitalization Era - Destiartono, Mohamad Egi; Renata, Almeira; Yoestini (Economic and Business Horizon, 2025)
The dynamic modern workplace and digitalization change the workforce from rigid to liquid workforces. Therefore, this study aims to unravel the characteristics, benefits, and challenges of fluid workers in Indonesia using a qualitative method. For these motivations, structured questionnaires with dichotomous questions were distributed to collect primary data. To avoid biased results, study participants are chosen rigorously. The number of participants was 15 workers from various institutions. The findings show that most fluid workers in Indonesia are adaptive, easy to collaborate with, tech-savvy, lifelong learners, and resilient. The current benefits of fluid workers include skill and knowledge exposure, networking possibilities, the prospect of higher income, and flexibility. In terms of challenges, a lack of benefits and limited social support are two factors that impede fluid workers. Surprisingly, job insecurity and income instability are not the primary concerns for fluid workers, indicating that fluid workers differ significantly from informal workers. The priority needs of fluid workers are the right to rest and leisure, equal treatment, fair compensation, and career development opportunities.